Assessment of the Turkish Version of the King's Stool Chart for Evaluating Stool Output and Diarrhea Among Patients Receiving Enteral Nutrition - Dag, Gulten Sucu; Dicle, Aklime; Saka, Osman; Whelan, Kevin (Lippincott Williams & Wilkins, 2015)
The purpose of this study was to evaluate the reliability and validity of the Turkish version of the King's Stool Chart (KSC-Tr) in patients receiving enteral nutrition. In total, 212 stool samples taken from 25 patients receiving enteral nutrition during 393 sick days in two intensive care units were assessed using the KSC-Tr. Overall, 110 of 212 stools (51.9%) were characterized as liquid and 111 of 212 stools (52.4%) were characterized as less than 100 g. The daily stool score of patients receiving antibiotics, a risk factor for diarrhea, was higher (mean = 13.6; SD = 10.1) than that of patients not receiving antibiotics (mean = 9.3; SD = 5.0) (p =.001). Diarrhea occurred on more days when patients received antibiotics (62/329; 18.8%) than on days when they did not (3/64; 4.7%) (p =.005). Interobserver agreement of two independent nurses' assessments on 44 stool samples was examined and was good for both stool consistency (kappa = 0.76) and stool weight (kappa = 0.75). In the intensive care unit, the KSC-Tr can be used as a valid and reliable tool for monitoring diarrhea and stool output in patients receiving enteral nutrition.
Keywords: Validity